Preferential apical infection and spread of human metapneumovirus highlights the importance of inhaled delivery of neutralizing monoclonal antibody to treat established infections - Karthik Tiruthani; Madison P. Card; Whitney Wolf; Limei Shen; Alison Schaefer; Marshall Fritz; Kenichi Okuda; Jack R. Harkema; Jarrod J. Mousa; Raymond J. Pickles; Samuel K. Lai (Proceedings of the National Academy of Sciences, 2025)
Human metapneumovirus (hMPV) is a frequent cause of acute respiratory infections in infants, the elderly, and the immunocompromised. No vaccines or treatments are currently available beyond supportive care. Building on our previous work with parainfluenza viruses and respiratory syncytial virus, we investigate the pattern of hMPV infection and spread in polarized and well-differentiated cultures of human airway epithelium (WD-HAE). We found productive infection of WD-HAE requires apical inoculation of hMPV, with infectious spread dependent on progeny viruses shedding into mucus secretions overlaying the apical surface of WD-HAE. A potent neutralizing monoclonal antibodies (mAb) against hMPV fusion protein—mAb364 (also termed MPV364)—prevented initial infection by hMPV and halted spread of established hMPV infection when dosed directly to the apical surface of WD-HAE. Conversely, mAb364 delivered to the basal compartment was unable to curb established infections, even at 100-fold greater concentrations. Intranasal delivery of mAb364 to hamsters with established hMPV infections reduced viral titers by ~four logs within 2 d and alleviated key pathological outcomes of hMPV infection. These results are consistent with hMPV infection and continued spread occurring via the apical surface of the respiratory epithelium, and underscore delivery of neutralizing mAbs to the respiratory tract as an effective intervention against established hMPV infections.